The Analysis of the Effectiveness of SMPIT Tunas Cendekia Profile Videos as Digital Promotion Media: Mixed Method Approach with Epic Model, Qualitative Interviews, and Youtube Analytics - Hariadi, Rudi; Yeni (Politeknik Negeri Batam, 2025)
In the era of digital competition, educational institutions are required to adopt innovative and technology-based promotional strategies. This study aims to evaluate the effectiveness of a school profile video of SMPIT Tunas Cendekia as a digital promotional medium to support student enrollment campaigns. A mixed-method approach was applied by integrating the EPIC Model (Empathy, Persuasion, Impact, Communication), qualitative interviews, and YouTube Analytics. Quantitative data were collected from 66 respondents using a Likert-scale questionnaire based on the EPIC Model, while qualitative insights were gathered through in-depth interviews with prospective parents and school representatives. Additionally, YouTube performance metrics such as view count, watch time, and click-through rate (CTR) were analyzed. The findings show that all four EPIC dimensions scored in the